Eficácia da solução de cloreto de sódio a 7,5% com e sem dextran 70 a 6% na preservação da função renal de cães hipovolêmicos submetidos à isquemia-reperfusão - Rodrigues Júnior, Geraldo Rolim (2002)
BACKGROUND AND OBJECTIVES: Sodium chloride hypertonic solutions, with or without hyperoncotic colloids, may be effective in protecting kidney against hypovolemia. This experiment aimed at evaluating, in dogs, the real benefit of these solutions on renal function in the presence of hypovolemia and ischemia. METHODS: Experiments were performed in 24 mixed-breed dogs anesthetized with sodium pentobarbital, submitted to right nephrectomy and volume expansion with Ringer s solution (1 ml.kg-1.min-1). Renal morphological and physiological changes were studied after 20 ml.kg-1 hemorrhage and 30 min of total left renal ischemia followed by reperfusion, in addition to renal repercussion of 7.5% NaCl (HS) and 7.5% NaCl in 6% dextran 70 (HSD). The following parameters were studied: HR, MBP, inferior vena cava pressure, renal blood flow, renal vascular resistance, hematocrit, Na+, K+, plasma osmolarity, PaO2, PaCO2 and pH; clearance (para-aminohipuric acid - PAH-1, creatinine, free water, osmolar, Na+ and K+), filtration fraction, urine output and osmolarity, sodium and potassium urine and fractionated excretions; rectal temperature; and kidney histopathology. Atributes where studied in five moments in three groups (G1, G2 and G3). RESULTS: There has been a statistically significant increase in mean blood pressure in G2 and G3. RVR was higher in G1; RBF and PAH clearance were higher in G3; Na+ fractionated excretion was increased in G2 and G3; creatinine, free water, osmolar, Na+ and K+ clearances, diuresis, and urinary excretions of Na+ and K+ were higher in G3. CONCLUSIONS: HSD infusion 15 min after mild hemorrhage and 30 min before ischemia was effective in protecting kidney of dogs from ischemia-reperfusion repercussions. There have been no histopathologic changes under optical microscopy.